The impact of platform leadership on employee deviant innovation in digital transformation enterprises - An-Jin Shie; En-Min Xu; Hongchun Li; Guanghai Yang; Yung-Fu Huang (Scientific Reports)
Abstract Platform leadership (PL) has been increasing in digital transformation enterprises. This study explores the effects, pathways, and boundary conditions of PL on employee deviant innovation (EDI). In this study, 444 valid questionnaires were collected from ten digital transformation enterprises. Using conservation of resources theory and digital leadership theory, we built a parallel mediation model in which PL influenced EDI through psychological safety (PS) and creative self-efficacy (CSE), and verified the moderating effect of digital leadership (DL). The empirical results are as follows: (1) PL positively impacts EDI. (2) PL positively influences PS and CSE. (3) PS and CSE positively contribute to EDI. (4) PS and CSE mediate the relationship between PL and EDI. (5) DL moderates the relationship between PL and EDI, as well as between CSE and EDI. This study departs from traditional leadership theories by examining a new leadership style, PL, to inspire deviant innovation behavior among employees in digital transformation enterprises. This reveals the influencing mechanisms and provides new theoretical support for leadership and innovation management.